Effects of a shallow SAS divertor on detachment in KSTAR. (2nd December 2020) - Ra, Ookjoo; Kwon, Kyu Been; Casali, Livia; Guo, Houyang; Stangeby, Peter C.; Hur, Min Sup
Abstract: For long pulse operation of fusion reactors, it is important to reduce sputter-erosion and power loading of the divertor target by means of plasma detachment. It has been reported that the small-angle-slot (SAS) divertor employed by the DIII-D tokamak can initiate detachment at a relatively low upstream plasma density as it can effectively dissipate heat by concentrating neutrals near the target. Motivated by these findings in DIII-D, we investigated the effects of a SAS-like divertor in KSTAR using SOLPS-ITER simulations without drifts. One remarkable feature revealed by our simulation study is that even a very shallow SAS can lead to a considerably lower heat load on the divertor target than the original flat, open divertor of KSTAR. Deuterium neutrals are concentrated along the divertor separatrix line in the shallow SAS, while deuterium density in the open divertor peaks in the far-scrape-off layer. Furthermore it was found that the neutral density and temperature-drop induced by SAS are both fairly incentive to the depth of the slot. The highest heat dissipation was obtained for a SAS depth of 10.3 cm.